First report of extended-spectrum β-lactamases TEM-116 and OXA-10 in clinical isolates of alcaligenes species from Kuala Lumpur, Malaysia - Puah, Suat Moi; Puthucheary, Savithri Devi; Chua, Kek Heng (Institute of Infectious Diseases, 2019)
There is an alarming increase in the prevalence of extended-spectrum β-lactamases (ESBLs) present mainly in Enterobacteriaceae and other nonfermenting gram-negative bacteria, such as Alcaligenes faecalis, which is the only species in that genus that is clinically relevant. We investigated Alcaligenes species from 7 cases (6 inpatients and one outpatient) at our tertiary-care hospital. Four patients had urinary tract infections, and one each had systemic lupus erythematosus, pulmonary stenosis, and diabetic ulcer. All 7 isolates were identified as Alcaligenes spp. based on their 16S rRNA gene sequences, and antibiotic susceptibility was determined using a Vitek 2 system with AST-GN87 cards. All the strains were resistant to cefazolin; 6 were resistant to trimethoprim/sulfamethoxazole; 5 manifested resistance to ampicillin/sulbactam, cefepime, tobramycin, ciprofloxacin, and nitrofurantoin; whereas 5 had multidrug resistance profiles. All the strains (7/7) expressed ESBL activity; PCR screening and sequencing showed evidence of genes blaTEM-116 (7/7) and blaOXA-10 (4/7), and we believe that this is the first report on the presence of TEM-116 and OXA-10 in an Alcaligenes spp. A combination of the 2 genes was present in 4 strains. All 7 strains were found to harbor at least one ESBL gene probably contributing to the drug resistance. © 2019, National Institute of Health. All rights reserved.